Cyber Counseling : Solusi Konseling di Masa Pandemi - Mariana Puspa Sari; Herdi Herdi (Jurnal Paedagogy, 2021)
This study aims to explore the role of cyber counseling during the pandemic for Counseling Guidance Teachers and students. This type of research is a literature study or library research using secondary data sources collected through textbooks, e-books, scientific articles, websites, and other sources relevant to the research problem. The data of this study were analyzed descriptively qualitatively. The results of this study indicate that through online-based BK services, students and BK teachers/Counselors can be mutually facilitated because there are many opportunities and benefits available in an effort to support the achievement of counseling goals. The presence of cyber counseling as a counseling solution during the pandemic is expected to be able to help solve student problems at this time.